School for bandits - Shaw, Hannah (New York : Knopf, 2011)
Ralph Raccoon is too polite so his parents send him to Bandit School to learn to behave like a properly bad raccoon.
Publisher's Weekly
Publisher's Weekly, May 2011
2.9
K-3
K-3
Keywords: Etiquette -- Juvenile fiction; Human behavior -- Juvenile fiction; Raccoon -- Juvenile fiction; Behavior -- Fiction; Etiquette -- Fiction; Raccoon -- Fiction; Etiquette -- Fiction; Human behavior -- Fiction; Raccoons -- Fiction; Picture books for children